T‐Wave Alternans and ST Depression Assessment Identifies Low Risk Individuals with Ischemic Cardiomyopathy in the Absence of Left Ventricular Hypertrophy. Issue 4 (3rd May 2013) - Friedman, Daniel J.; Bender, Seth R.; Markowitz, Steven M.; Lerman, Bruce B.; Okin, Peter M.
<x xml:space="preserve">Abstract</x> Background Although ECG left ventricular hypertrophy (LVH) by Cornell product (CP) predicts increased mortality in patients with ischemic cardiomyopathy (ICM), those without CP LVH remain at relatively high risk. We examined whether T‐wave alternans (TWA) testing and ST depression can improve risk stratification in these patients. Methods and Results This study examined 317 patients with ICM, nonsustained ventricular tachycardia, and a resting ECG in sinus rhythm, who presented for electrophysiology and TWA testing, and potential implantable cardioverter defibrillator (ICD) implantation. LVH was defined by CP :[(RaVL + SV3) +6 mm in women] × QRS duration > 2440 mm * msec. ST depression was examined as a categorical variable using an established threshold of depression of ≥50 μV in V5 or V6. In Cox multivariate models, abnormal TWA testing and ST depression were independent predictors of mortality in patients without CP LVH (HR 2.52, CI 1.09–5.80, P = 0.030 and HR 2.87, CI 1.41–5.81, P = 0.004, respectively). Individuals with no LVH by CP, normal TWA, and no significant ST depression, comprised 23% of the study population and had a 5.6% 3‐year mortality, compared to an overall 20% mortality. Conclusions TWA and ST depression testing are strong predictors of mortality among ICM patients without CP LVH, with normal testing conversely predicting low 3‐year mortality. Thus, risk assessment with TWA testing and a resting ECG can identify ICM patients at low risk who may be less likely to benefit from ICD implantation.